A Comparative Study of the Reverse Sural Fascio-Cutaneous Flap Outcomes in the Management of Foot and Ankle Soft Tissue Defects in Diabetic and Trauma Patients. Issue 5 (October 2019) - Assi, Chahine; Samaha, Camille; Chamoun Moussa, Moussa; Hayek, Tony; Yammine, Kaissar
Introduction . Soft tissue defects in the distal leg and foot are challenging conditions for reconstruction. The widely used reverse sural fascio-cutaneous flap (RSFCF) has been reported with large variation in complication frequency. Some authors reported higher complications in the diabetic population when compared with trauma patients. We compared the reliability of the RSFCF in treating such defects among both populations. Methods . This is a retrospective series with a prospective data collection of 24 patients (11 with type 2 diabetes and 13 in trauma settings) treated with an ipsilateral RSFCF for soft tissue defects of the distal leg and the rear foot. Healing events and complications were recorded and compared for both groups. The mean follow-up was 32 months. Results . Diabetic group versus trauma group showed the following results; mean flap healing time of 24 versus 22 days, donor site healing time of 14 versus 16 days, 1 total flap necrosis in both groups, 3 versus 2 cases of skin edge necrosis, 2 cases of temporary venous congestion in both groups, and 8 versus 10 cases of transient hypoesthesia of the lateral border of the foot. No infection was encountered in both groups and no recurrence of infection in the primary infected diabetic patients. Conclusions . We found the RSFCF to be useful, reproducible, and reliable in treating soft tissue defects with a very low frequency of serious complications. Diabetic patients were found to have similar outcomes when compared with trauma patients. Therefore, diabetes might not be a major factor of flap failure. Levels of Evidence: Level III: Therapeutic